1994
DOI: 10.1002/bjs.1800810723
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal bezoars

Abstract: Of 99 patients with 117 gastrointestinal bezoars, 69 had undergone previous surgery, the most common operation being bilateral truncal vagotomy with pyloroplasty (55 patients). An excessive intake of vegetable fibre was found in 38 patients and poor mastication in 27. Thirty bezoars presented with gastric symptoms and patients had endoscopy as the diagnostic technique; 87 caused symptoms of intestinal obstruction with the diagnosis made by plain abdominal radiography. Medical treatment by enzymic or endoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 17 publications
1
74
0
3
Order By: Relevance
“…Major complications of BZs include intestinal obstruction, gastric perforation, gastric ulcer, gastritis [6,[23][24][25] . SBO is the most common complication and requires surgery [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Major complications of BZs include intestinal obstruction, gastric perforation, gastric ulcer, gastritis [6,[23][24][25] . SBO is the most common complication and requires surgery [3] .…”
Section: Discussionmentioning
confidence: 99%
“…They most often develop in patients who have undergone gastric resection or ulcer surgery [16]. Studies have shown that more than 75% of patients who develop gastric or small bowel bezoars have a past history of surgery for peptic ulcer disease [17]. In accord with the literature, our patient had undergone gastric resection.…”
Section: Discussionmentioning
confidence: 88%
“…Since there is abdominal surgery history in most of the patients, it can be misleadingly thought that obstruction related to adhesion develops (6). Epigastric pains imitating peptic ulcer activation in gastric bezoars or upper gastro-intestinal system bleeding and perforation due to bezoar eroding mucosa might be observed (7). Time between the first surgery and phytobezoar formation is generally more than 10 years.…”
Section: Discussionmentioning
confidence: 99%